Effectiveness of Learning and Teaching by E-learning Lessons for Bachelor of Public Health Program - Vichean, Ubonrat; Thummanon, Thassanan; Meesuk, Nattaporn; Ranurak, Thosaporn (Journal of The Royal Thai Army Nurses, 2020)
The research aimed to study Effectiveness of learning and teaching by E-learning lessons for Bachelor of Public Health Program students Department of Dental Public Health Sirindhorn Public Health Chonburi Province. The sample of this research were a second- year students. Who were studying Bachelor of Public Health Program of the academic year 2019 the total of 31 samples. By using E-learning lessons in first aid The study period was 6 months. Data were analyzed by percentage, mean, standard deviation and comparison of results within the experimental group. Statistics using Paired samples t - test. The results of the research showed that 1) The samples after the intervention an average knowledge scores higher than before intervention (p < .05) 2) The samples groups after the intervention an average more behavior scores higher than before intervention. (p < .05) 3) The samples group after the intervention an average more mean score on satisfaction with E-learning lessons higher than before intervention (p < .05)